Mesopause region thermal and dynamical studies based on simultaneous temperature, zonal and meridional wind measurements with an upgraded sodium fluorescence lidar - Sherman, James Patrick, author; She, Chiao-Yao, advisor; Krueger, David A., advisor; Harton, John, committee member; Lundeen, Stephen, committee member; Johnson, Richard H., committee member (Colorado State University. Libraries, 2002)
Continued hardware upgrades have permitted extension of the Colorado State University (CSU) lidar to a two-beam operation, capable of simultaneously measuring temperature, zonal winds, meridional winds, and sodium density in the mesopause region (80-105km) above Fort Collins, CO. A total of 172 hours of nightly observation and four campaigns over full diurnal (24-hour) cycles have been conducted in this two-beam configuration. The nighttime results, composed of 70 observation hours during the winter period of Jan. 26-Feb. 15, 2002 and 102 hours during the early summer period of May 22-June 12, 2002 are compared with temperature and wind climatology models and with Hata compiled from four decades of sparse wind measurements made by tracking metallic chemicals released by rockets (compiled by Larson, 2001). Large winter winds and shears and the resulting instabilities (in the Richardson sense) can be inferred from the data. These winds are larger than those predicted in models (Hedin, Robie) and are comparable to chemical release data (Larson). During the period May 22-June 12, the CSU lidar measured mesopause region temperatures, zonal winds, and meridional winds ova four full diurnal cycles (the first such simultaneous measurements covering complete diurnal cycles). These measurements were part ofa 232-hour campaign. Harmonic analysis was performed on the resulting temperature and wind measurements and the resulting amplitudes and phases of the 12 and 24-hour oscillations were compared with those from the Global-Scale Wave Model (GWSM00) created (1995) and upgraded by Hagan.
Keywords: optics; atmosphere; remote sensing; geophysics